Bidirectional mechanobiology between cells and their local extracellular matrix probed by atomic force microscopy. (January 2018) - Alcaraz, Jordi; Otero, Jorge; Jorba, Ignasi; Navajas, Daniel
Abstract: There is growing recognition that the mechanical interactions between cells and their local extracellular matrix (ECM) are central regulators of tissue development, homeostasis, repair and disease progression. The unique ability of atomic force microscopy (AFM) to probe quantitatively mechanical properties and forces at the nanometer or micrometer scales in all kinds of biological samples has been instrumental in the recent advances in cell and tissue mechanics. In this review we illustrate how AFM has provided important insights on our current understanding of the mechanobiology of cells, ECM and cell-ECM bidirectional interactions, particularly in the context of soft acinar tissues like the mammary gland or pulmonary tissue. AFM measurements have revealed that intrinsic cell micromechanics is cell-type specific, and have underscored the prominent role of β1 integrin/FAK(Y397) signaling and the actomyosin cytoskeleton in the mechanoresponses of both parenchymal and stromal cells. Moreover AFM has unveiled that the micromechanics of the ECM obtained by tissue decellularization is unique for each anatomical compartment, which may support both its specific function and cell differentiation. AFM has also enabled identifying critical mechanoregulatory proteins involved in branching morphogenesis (MMP14) and acinar differentiation (α3 β1 integrin), and has clarified the role of altered tissue mechanics and architecture in a variety of pathologic conditions. Critical technical issues of AFM mechanical measurements like tip geometry effects are also discussed.